Pancreatic abscess: a modern look at an old problem - Fedir Prytkov; Denis Yurkin (Bogomolets National Medical University, 2022)
analysis of morphological and etiologic characteristics and clinical features of pancreatic abscesses on the basis of previous publications.  Theoretical analysis and generalization, classification, analysis of scientific and methodical literature. The analysis of the literature was carried out using electronic scientometric database Scopus, Web of Science, Ulrich's Periodicals, Google Scholar, PubMed, Medline. We analyzed literary sources publicated since 1909, using the keywords, such as: pancreatic abscess, abscess of pancreas. Articles published in professional English-language journals were included. Were analyzed publications dedicated to acute pancreatitis, chronic pancreatitis, infected pseudocysts as a cause of pancreatic abscess. We analyzed scientific works concerning benign and malignant tumors of pancreaticoduodenal area, scientific papers concerning fish bone penetration into the pancreas. Causes of pancreatic abscess development such as trauma of the pancreas, thrombosis of a.lienalis and pancreas divisum were described in the publication for the first time. Other scientific works are devoted to infectious agents, diagnosis and treatment of abscesses. Pancreatic abscess is the body's response to pancreatic infection that is characterized by specific morphological structure and heterospecific etiology. Pancreatic abscess is the transition state that combines acute destructive (acute infected necrotizing pancreatitis) and chronic degenerative (a chronic fibrotic-degenerative pancreatitis complicated by the pancreatic pseudocyst) pancreatitis. Pancreatic abscess can be considered as the marker of chronization of inflamantory and destructive pathological processes that need etiologic authentication and further treatment.